PENGEMBANGAN HANDOUT BERGAMBAR DISERTAI PETA KONSEP PADA MATERI EKOSISTEM UNTUK SISWA SMP/MTs - silvia, Mega - (STKIP PGRI Sumbar, 2014)
The learning process requires a learning media in term of teaching materials. One type of teaching materials thatcan be used by teachers is through illustrated handout which accompanied by concept mapping. Handouts arewritten teaching materials taken from several literature that relevant to the basic competencies and subjectmatter taught to the students. But the teaching materials used by teachers in MTsN Talaok Shaded is lessattractive because the picture just shown in black and white, not accompanied with concept mapping, thedrawing only represent a few of the all material and also too concise. This is causes less motivationon studentsto learn and it is difficult to them to distinguish the basic concepts of the material which contained on theecosystem matter. Based on that situation, the developing an instructional materials in the form of illustratedhandout accompanied by concept mapping on the ecosystem matter has choosen. This study aims to determinethe validity and practicalities illustrated handout with a concept mapping. This study uses a model of thedevelopment of type 4-D. Model development consists of 4 stages; Define, Design, Development andDisseminate. This study is only conducted to Development stage. The data used are primary data which is dataobtained directly from lecturers, teachers and students, which consists of 4 people validator, 2 teachers and 20students MTsN Talaok Bayang. Research results obtained is the average value of test validity by faculty andteachers is 86.02% with a valid criteria. This handout feasibility measured from various aspects, such asfeasibility of content, language, presentation and graphic. The average value of the practicalities testing byteacher is 88.19% with a very practical criteria. This handout practicality measured from several aspects: ease ofuse, effectiveness and presentation of learning time. While the average value of the practicalities testing bystudents is 93.63% with a very practical criteria and the practicality of handouts was measured from variousaspects: ease of use, effectiveness and presentation of learning time. Based on this data, we can conclude thatthe handouts has been valid and very practical.